Purification of dye industries wastewater via crystallization: effect of operation temperature and solution flow rate - Mohd Ibrahim, Nur Shahirah (2018)
Dye industry is one of the industries that generates huge amount of wastewater and contributes to environmental devastation. Various ways have been used in wastewater treatment to make it less harmful. This study aimed to purify dye industries wastewater via a method of crystallization known as progressive freeze concentration (PFC). PFC is a crystallization process that forms only one single block of ice making it easier to be separated with the mother liquor solution. The effect of operation temperature and solution flow rate (stirring speed) was investigated in this study. The performance analysis was carried out by using simulated solution and was evaluated by the value of effective partition constant, K and percentage of ice purity. It was found that at temperature of -8˚C, the K value obtained of 0.2615 was the lowest with the highest percentage of ice purity of 71.55%. It was also notable that the best stirring speed to achieve highest efficiency was at 350 rpm with a K value of 0.3343 and ice purity percentage of 62.69%.